Papillary thyroid carcinoma with biomineralization: clinical and morphological features - R. A. Moskalenko; A. M. Romaniuk; A. V. Rieznik; A. V. Kurochkin; A. M. Piddubniy; V. A. Lukash (Patologìâ)
Papillary thyroid cancer (PTCa) is the most common form of malignant tumors of this organ, covering approximately 70% in the structure of morbidity. Pathological biomineralization is often the first diagnostic sign of ultrasound of the thyroid, so the study of its morphological features is the purpose of our paper. A total of 30 PTCa samples with the signs of biomineralization and 30 PTCa samples without biomineralization were studied. The study used histological, histochemical techniques and scanning electron microscopy with X-ray diffraction. All PTCa patients who had the signs of pathological biomineralization were combined in the first group (30 people) – 27 women and 3 men (9:1). The average age of patients of the first group was 56.93±2.18 years old. The patients were diagnosed with different histological PTCa types: 22 cases of classic variant of PTCa, 3 cases of diffuse sclerotic variant, 2 cases of follicular, 2 cases of tall cell variant, and 1 case of solid variant of PTCa. Patients who had no signs of PTCa mineralization, made up the second group. 30 people – 24 women and 6 men (4:1) – were selected in to the second group. It was found out that in the first group the largest size of tumor site averaged 1.84±0.13 cm, and in the second group the rate was 1.44±0.09 cm (p<0.07). Comparing the number of patients with metastases in both groups (7 – I group, 8 – Group II) and describing the size of tumor nodules, subject to presence of metastases in patients (2.09±0.2 cm and 1.31±0.17 cm), there was significant difference found between indicators of clinical cases of studied groups (p<0.02). The main mineral that is involved in the development of dystrophic calcification in case of PTCa is hydroxyapatite. The presence of hydroxyapatite is characteristic for all the types of PTCa biomineralization.